The Determinants of Islamic Rural Banks’ Efficiency in Indonesia - Wastuti, Wahyu; Thalib, Herni Ali Husin; Fitrijanto, Arief (International Journal of Islamic Economics and Finance (IJIEF), 2025)
Given the critical role of Islamic Rural Banks (IRB) in supporting financial inclusion and economic stability in Indonesia, this research urgently highlights the need for strategic improvements in IRB efficiency to ensure sustainable growth and resilience in the face of economic uncertainties. This research aims to assess the effectiveness of Islamic Rural Banks (IRB) in Indonesia. In the second phase, the study examines the impact of Risk Profile, Good Corporate Governance (GCG), Earnings & Capital (RGEC) factors on IRB efficiency. Additionally, the research analyzes the influence of the Maqasid Sharia Index (MSI) on IRB efficiency. The methodology involves employing Data Envelopment Analysis (DEA) followed by a Multinomial Logistic Regression test, using a sample of 119 IRB across Indonesia. The research period of this article is from the fourth quarter of 2019 to the fourth quarter of 2021. The DEA results categorize 516 and 693 data observations as high efficiency for intermediation and production approaches, respectively. Risk Profile factors (NPF & FDR) significantly affect IRB efficiency. GCG factors, specifically Board of Directors’ Ownership & Board of Commissioners’ Ownership, have a significant impact on IRB efficiency, but only in the intermediation approach. Earnings, represented by ROA, significantly influence both approaches, while ROE yields opposite results. Capital, represented by CAR, significantly affects the intermediation approach. The Sharia factor, MSI, demonstrates a significant impact on IRB efficiency in both intermediation and production approaches. These findings serve as an academic reference for IRB managers, guiding decision making to enhance efficiency in the future.